Changes induced by diet and nutritional intake in the lipid profile of female professional volleyball players after 11 weeks of training - Mielgo-Ayuso, J.; Collado, P. S.; Urdampilleta, A.; Martinez-Sanz, J. M.; Seco, J. (Journal of the International Society of Sports Nutrition, 2013)
The relationship between cardiovascular disease and lipid profile is well known. Apart from a heart-healthy diet, exercise is the primary factor that can modify this lipid-associated cardiovascular risk. The aim of the study was to evaluate potential changes in the levels of triglycerides, total cholesterol (TC), low-density lipoprotein-cholesterol (LDLc), and high-density lipoprotein-cholesterol (HDLc), as well as atherogenic indices (TC/HDLc and LDLc/HDLc), and also to analyse the diet over 11 weeks of training in female professional volleyball players. Methods: The lipid profile of 22 female professional volleyball players was analysed on Day T0 (pre-preseason) and Day T11 (after 11 weeks of training). The consumption of fats by the players was estimated using a food frequency questionnaire, confirmed by seven days of full dietary records. Results: By the end of the study, the LDLc levels and both atherogenic indices of the players had decreased (p?<?0.05) compared to the values obtained at baseline. In addition, the diet of the players contained 35.5 ± 3.2% of fats (saturated fatty acid: 11.1 ± 1.2%, monounsaturated fatty acid: 14.3 ± 1.9%, and polyunsaturated fatty acid: 7.0 ± 1.1%) and 465 ± 57 mg of dietary cholesterol. Their score for the (monounsaturated + polyunsaturated fatty acid)/saturated fatty acid ratio was 1.9?±?0.4, less than the recommended = 2. Conclusion: These data indicate that the activity of the female professional volleyball players during the first 11 weeks of training in the season was heart healthy, because their lipid profile improved, despite an inadequate intake of fats.